Potassium levels and short-term outcomes in heart failure with mildly reduced ejection fraction - Reinhardt, Marielen; Behnes, Michael; Weidner, Kathrin; Ayasse, Niklas; Lau, Felix; Schmitt, Alexander; Abel, Noah; Dudda, Jonas; Bertsch, Thomas; Dürschmied, Daniel; Akın, Ibrahim; Schupp, Tobias (International journal of cardiology, 2025)
Objective - The study investigates the prognostic impact of dyskalemias in patients hospitalized with heart failure with mildly reduced ejection fraction (HFmrEF). - Background - Although dyskalemias represent a common complication in patients with heart failure (HF) and reduced left ventricular ejection fraction (LVEF), data concerning the prevalence and prognostic impact of dyskalemias in HFmrEF is limited. - Methods - Consecutive patients with HFmrEF were retrospectively included at one institution from 2016 to 2022. The prognostic impact of potassium levels was assessed comparing patients with potassium levels > 3.3 to ≤4.5 mmol/L, ≤3.3 mmol/L and > 4.5 mmol/L. The primary endpoint was all-cause mortality at 30 days. - Results - 2079 patients with HFmrEF and potassium measurement were included (median potassium level: 4.4 mmol/L; mean 4.2 mmol/L). 84 % of patients hospitalized with HFmrEF presented with potassium levels in the norm range, 8 % with hypokalemia and 8 % with hyperkalemia, respectively. The risk of all-cause mortality at 30 days was higher in patients with hyperkalemia compared to patients with normokalemia (7 % vs 4 %; log rank p = 0.026), whereas the presence of hypokalemia (6 %; log rank p = 0.075) was not significantly associated with the risk of 30-days all-cause mortality. Compared to patients with normokalemia, the presence of hyperkalemia was still associated with an increased risk of 30-day all-cause mortality within a multivariable Cox regression analysis (HR = 2.002; 95 % CI 1.004-3.992; p = 0.049). - Conclusion - In patients hospitalized with HFmrEF, hyperkalemia - but not hypokalemia - was independently associated with an increased risk of all-cause mortality at 30 days.
Online verfügbar: 3. Dezember 2024, Artikelversion: 12. Dezember 2024
Gesehen am 29.04.2025